Un caso di effettività perduta: la legge n. 40/2004 e la doppia maternità (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay investigates the legal consequences of the loss of effectiveness of law n. 40/2004 in cases of recognition of double motherhood of children born in Italy from a homogenous-relational project carried out abroad: first, the repercussions on the principles of legality, equality and legal certainty in the face of multiple jurisprudential orientations on the subject, and secondly, the “fate” of the limit ex art. 5 law 40 in the absence of an organic intervention of the legislature to protect the rights of children born from a homogenous project.
Keywords: Medically Assisted Reproduction; procreative tourism; intentional mother; best interests of the child; separation of powers